Effects of religious vs. standard cognitive behavioral therapy on therapeutic alliance: A randomized clinical trial. (3rd May 2016) - Koenig, Harold G.; Pearce, Michelle; Nelson, Bruce; Shaw, Sally; Robins, Clive; Daher, Noha; Cohen, Harvey Jay; King, Michael B.
Abstract: Background: Treatments that integrate religious clients' beliefs into therapy may enhance the therapeutic alliance (TA) in religious clients.Objective: Compare the effects of religiously integrated cognitive behavioral therapy (RCBT) and standard CBT (SCBT) on TA in adults with major depression and chronic medical illness.Method: Multi-site randomized controlled trial in 132 participants, of whom 108 (SCBT = 53, RCBT = 55) completed the Revised Helping Alliance Questionnaire (HAQ-II) at 4, 8, and 12 weeks. Trajectory of change in scores over time was compared between groups.Results: HAQ-II score at 4 weeks predicted a decline in depressive symptoms over time independent of treatment group ( B = −0.06, SE = 0.02, p = 0.002, n = 108). There was a marginally significant difference in HAQ-II scores at 4 weeks that favored RCBT ( p = 0.076); however, the mixed effects model indicated a significant group by time interaction that favored the SCBT group ( B = 1.84, SE = 0.90, degrees of freedom = 181, t = 2.04, p = 0.043, d = 0.30).Conclusions: While RCBT produces a marginally greater improvement in TA initially compared with SCBT, SCBT soon catches up.